Self-construal priming modulates sonic seasoning - Xu, Jingxian; Guo, Xiyu; Liu, Mengying; Xu, Hui; Huang, Jianping (Frontiers in Psychology, 2023)
“Sonic seasoning” is how music can influence consumers' real tasting experiences. “Self-construal” is how individuals perceive, understand, and interpret themselves. Numerous studies have shown that independent and interdependent self-construal priming can affect a person's cognition and behavior, however their moderating effect on the sonic seasoning effect remains unclear. Therefore, this study explored the moderating role of self-construal priming in the effect of emotional music on real food tasting by comparing participants' evaluations of chocolates while listening to positive or negative music after different levels of self-construal priming. The results showed that after initiating independent self-construal, participants increased their ratings of milk chocolate sweetness when listening to music that elicited positive emotions. In contrast, interdependent self-construal priming led participants to perceive dark chocolate as sweeter when they heard positive music. In conclusion, this study provides evidence for improving the individual eating experience and enjoyment.